Decoding low-density parity check codes with normalized APP-based algorithm - Jinghu Chen; Fossorier, M.P.C. (2001 IEEE Global Telecommunications Conference - Globecom, 2001)
We propose a normalized a posteriori probability (APP) based algorithm for the decoding of low-density parity check (LDPC) codes. The normalized APP-based algorithm utilizes normalization to improve the accuracy of the soft values delivered by the simplified APP-based algorithm from one iteration to another during the iterative decoding, and can achieve very good tradeoff between decoding complexity and performance.